2019
DOI: 10.1111/pai.13045
|View full text |Cite
|
Sign up to set email alerts
|

Do traditional fermented foods protect against infantile atopic dermatitis

Abstract: Background: Environmental and dietary factors during pregnancy may affect development of infantile atopic dermatitis (AD). This study analyzed whether maternal consumption of selected Turkish fermented foods (FF) and other factors during pregnancy affect the development of AD during the first 2 years of life.Methods: Eighty-four children with physician-diagnosed AD (aged between 2 and 24 months) and mothers, and 56 similarly aged, healthy children and mothers were studied. Physician-administered questionnaires… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 31 publications
0
28
0
Order By: Relevance
“…Such markers have been shown to extend beyond maternal use and are present during early infant life. Coupled with a varied diet and other fermented foods, probiotic yogurt has been shown to reduce the risk of developing atopic dermatitis in early infancy [12]. Fecal studies have demonstrated the role of probiotics such as yogurt in the promotion of beneficial gut flora variants and healthy gastrointestinal maturation [15].…”
Section: Review Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Such markers have been shown to extend beyond maternal use and are present during early infant life. Coupled with a varied diet and other fermented foods, probiotic yogurt has been shown to reduce the risk of developing atopic dermatitis in early infancy [12]. Fecal studies have demonstrated the role of probiotics such as yogurt in the promotion of beneficial gut flora variants and healthy gastrointestinal maturation [15].…”
Section: Review Of Studiesmentioning
confidence: 99%
“…Yogurt has been commonly cited as a prospective option for further trials due to its worldwide availability, nutritional benefit, and potential for live microorganism delivery [11]. Limited studies have investigated the role of probiotic yogurt in the prevention and management of adverse pregnancy-related events such as gestational diabetes, preeclampsia, congenital anomalies, preterm birth, and infantile metabolic disorders [5,12,13]. This literature review aims to analyze the benefits of probiotic yogurt on improving maternal health and pregnancy outcomes and to further identify possible areas of study.…”
Section: Introductionmentioning
confidence: 99%
“…A study analyzed whether maternal consumption of selected Turkish fermented foods and other factors during pregnancy affect the development of atopic dermatitis during the first 2 years of life. Daily maternal intake of yogurt and diversity of consumed Turkish fermented foods during pregnancy may reduce the risk of atopic dermatitis [26 ].…”
Section: Allergic Diseasesmentioning
confidence: 99%
“…These reduced atopic dermatitis symptoms in a range going from high (for Mix 1) to a low certainty of evidence (for Lactobacillus casei DN‐114001). The treatment of atopic dermatitis by probiotics has been addressed earlier in PAI, 18 and interestingly another approach with Turkish traditional fermented foods has been validated 19 . Bacteria may also influence allergies through microbial‐derived products 20 and indirectly by breastmilk consumption 21 .…”
mentioning
confidence: 99%